What causes trainees to leave oral and maxillofacial surgery? A questionnaire survey. Issue 1 (January 2017) - Herbert, C.; Kent, S.; Magennis, P.; Cleland, J.
Abstract: Understanding what causes trainees to leave OMFS is essential if we are to retain them within the specialty. Although these factors have been defined for medicine, we know of no previous study for OMFS. An online survey was distributed to roughly 1500 people who had registered an interest in OMFS during the past seven years. Personal information and details of education and employment were gathered along with personal factors that attracted them to OMFS. Of 251 trainees who responded, 50 (30%) were no longer interested. Factors that significantly correlated with an interest in OMFS included male sex (p = 0.020), dual qualification (p = 0.024), and (only for women) being single (p = 0.024) and having no dependants (p = 0.005). We used qualitative analysis to identify work-life balance, duration of training, and financial implications, as significant factors. Identification of key factors that affect OMFS trainees allows us to develop ways to keep them in the specialty. The predominant factor is work-life balance, and for women this included having children and being married. Financial issues related to the junior doctors' contract and competition ratios to second degrees, are also factors for both sexes. Also important are the "sunk costs" fallacy that causes some trainees to stay in training. This information can be used to help develop higher training, in negotiations of contracts, and to attract and retain future OMFS trainees.